2021
DOI: 10.1016/j.ejor.2020.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Scheduled service network design with quality targets and stochastic travel times

Abstract: We address the stochastic scheduled service network design problem with quality targets and uncertainty on travel times. This important problem, raising in the tactical planning process of consolidation-based freight carriers, has been little studied up to now. We define the problem considering quality targets for on-time operation of services and delivery of demand loads to destinations. We introduce a two-stage mixed-integer stochastic model defined over a space-time network, with quality targets modeled thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Service failure could lead to a negative impact on travel destinations. The previous studies indicated that tourists’ travel risk and management perception may negatively influence tourists’ decision making [ 35 , 36 ]. Professional service delivery and timely response could reduce tourists’ travel risk and management perceptions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Service failure could lead to a negative impact on travel destinations. The previous studies indicated that tourists’ travel risk and management perception may negatively influence tourists’ decision making [ 35 , 36 ]. Professional service delivery and timely response could reduce tourists’ travel risk and management perceptions.…”
Section: Literature Reviewmentioning
confidence: 99%
“… Alsmadi et al., 2012 ; Berardino and Onesti, 2020 ; Brueckner and Flores-Fillol, 2020 ; Dias et al., 2020 ; Liao, 2020 ; Mathieu, 2001 ; Wang et al., 2003 ; Yuen and Chan, 2010 ) have been somehow stopping short when it came to outrightly integrate and acknowledge the critical role of SQ in the manufacturing (e.g. garments manufacturing industry in our case) sector ( Alsmadi et al., 2012 ; Berardino and Onesti, 2020 ; Dias et al., 2020 ; Lanza et al., 2021 ). As a result, over the period this disintegration of SQ in two different sectors (i.e.…”
Section: Literature Reviewmentioning
confidence: 96%
“…service sector and manufacturing sector) has led to an unending ordeal of poor SQ in the manufacturing sector ( Berardino and Onesti, 2020 ; Dias et al., 2020 ; Rosenzweig et al., 2019 ). Although, in a theoretical point of view only service sector/service industry seems to be more concerned with the delivery of SQ ( Lanza et al., 2021 ; Mandhani et al., 2020 ; Peng et al., 2014 ; Qin et al., 2010 ). However, this study argues that inseparable and inextricable nature of service (see Parasuraman et al., 1985 , p. 42) from it’s origin/providers warrants a premeditated integration of SQ in the manufacturing sector ( Dias et al., 2020 ; Ertekin et al., 2020 ; Farooq et al., 2018a ; Wang et al., 2003 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Service arcs represent scheduled services, providing capacity for a set of commodities transported over transportation assets. The SND models have been employed in maritime transportation [19], rail transportation [20], land-based long-haul transportation [21], tactical planning of parcel delivery with autonomous vehicles [22,23], air freight parcel delivery [24,25], intermodal transportation [26], bus schedules [27], and service quality improvement [28].…”
Section: Literature Reviewmentioning
confidence: 99%